DAMPAK KRISIS KEUANGAN GLOBAL TERHADAP STABILISASI HARGA DAN OUTPUT DI INDONESIA: Analisis Bauran Kebijakan Sederhana - Samsul Arifin (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The enactment of the ITF, which has been strengthened by the FITF framework since 2010 amid the global financial crisis, is a test for the Central Bank in using interest rates as the only monetary policy operational target. The decline in liquidity in the Indonesian economy from the impact of the global financial crisis must be responded by Bank Indonesia to maintain credit growth. The monetary and macroprudential policy mix is carried out to maintain the momentum of economic growth with controlled inflation at low and stable levels while at the same time under pressure in the banking sector after the 2008 global financial crisis. This research directly examines the macroeconomic structural model by incorporating the crisis value into exogenous and credit-efficient variables. as a proxy for macroprudential policy. The purpose of this research is related to looking at the monetary policy response of the operational interest rate target as the optimal policy rule for the stabilization of prices and output in Indonesia from the impact of the global financial crisis using a macro structural cointegrating VAR design model State Contingent Rule (SCR).The results showed that the 2008 global financial crisis affected the optimal policy response through a simple policy mix in stabilizing prices and output. Monetary policy through the BI Rate operational target can stabilize prices in a relatively fast time given the size of its contribution in shaping the price component, but not better for output. The credit gap instrument in macroprudential can stabilize output in a fast and permanent time but with a very small contribution but it is not effective for price stabilization. The effective time of monetary policy in influencing price and output stabilization is up to 2.5 years.